Zagadnienie podstaw do wszczęcia procedury impeachment przeciwko urzędnikom federalnym w prawie i praktyce ustrojowej Stanów Zjednoczonych - Jaskiernia, Jerzy (Wydział Prawa i Administracji UAM, 1975)
The author begins his analysis with the statement that a constitutionally valid distinction between activities which are and are not subject to impeachment is not clear, and in consequence controversial. The interpretation of high crimes and misdemeanors is particularly open to doubt. It is debated whether impeachment applies solely to criminal offences or whether the mere breach of that highest degree of confidence as enjoyed by a public executive, especially the President of the United States, constitues a sufficient ground for action. Drawing on the English tradition as well as the opinions of Alexander Hamilton and James Madison, the autor favours a broad interpretation of the premises justifying impeachment — nevertheless he stresses the fact that it is not tantamount to giving leave to get round the relevant formulas of the constitution. Since the Constitution does not decide expressis verbis on who holds the right to interpret unclear premises, it has to be accepted — following Gerald R. Ford — that this right belongs to the House of Representatives which exercises the right of making indictments. The author extends this view by pointing to the fact that as the House of Representatives is a competent interpreter in the indictment phase, so the Senat will replace it during the phase of passing judgment; the function of the latter will be to check whether the subsumption of the constitutional norm and the actual facts has been carried out properly. The author indicates that interpretation in court is not involved here because the whole impeachment procedure has been placed within the powers of the Congress, and so an argument concerning it cannot appear in court which could only in that situation decide on an interpretation. Since there have been many attempts to interpret the grounds of starting an impeachment procedure in connection with particular party interests, the author examines the validity of the comparison between impeachment and a vote of confidence characteristic for the Parliamentary Cabinet systems. Rejecting the alleged similarity, the author points out that impeachment is different from a vote of confidence in the following 3 counts: 1) the motion must have a justification claiming the applicability of certain constitutional premises, 2) to achieve a removal from office it is necessery to secure a 2/3 majority in the Senate, 3) the effect of a removal (in the case of a president) is merely the replacement of the chief executive, while his party remains in office, with the exception of sporadic situations when the vice-president represents the opposition (as was the case during Lincoln's term of office). The author also rejects the claim that impeachment is a „check" in the separation of power system, or a factor in keeping the balance between its branches. To prove his point he brings up the following arguments: 1) as far as typical „checks" (like the president veto) are applicable in terms of normal execution of the law and as they are not something negative they only introduce certain rules of the game that goes on between the three divisions of government, impeachment, on the other hand, appears only in a „pathological" state of affairs caused by an offence or same other reprehensible behaviour, 2) the system of „checks" applies to the government as such and has a continuous operative power, whereas impeachment can be used. only against particular persons if their activities in office provide grounds for starting the procedure, 3) the idea of „checks" is bound with the intention of creating a situation in which the co-operation of two or more participants for the processes of decision-making is necessary, whereas in case of impeachment only the individual activity of Congress is involved, 4) impeachment can apply not only to the president and other representatives of the Executive but also to Federal Judges or even — as it was shown by the case of Blount — to membres of Congress, although in this last case it has lost its importance since Congress posseses more flexible disciplinary means. The author states in his conclusion that the significance of the institution of impeachment lies undoubtedly in its capability to act preventively with regard to breaches of law, but it is not, however, a typical check in the framework of division of power system, since its functioning in the aspect of constitutional and political structures is different.
The Problem of the Basis of Taking the Impeachment Procedure Against Federal Officials in the Law and Governmental Practice of the United States